Design and Implementation of a Mini Plant Water Level Controller Using PID with LabVIEW Integration and Arduino UNO - Buwarda, Sukriyah; Mutmainnah, Mutmainnah; Lutfi, Lutfi; Chang, Ming-Chung (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2025)
The Process Control Systems course, newly introduced in the 2022 ATI Makassar Polytechnic curriculum, emphasizes applied control practices to strengthen students’ understanding of process regulation. This study develops a teaching module for water tank level regulation using Proportional Integral Derivative (PID) control implemented through LabVIEW and Arduino Uno. Employing a Research and Development (R&D) approach with the DEDTE framework (Define, Explore, Design, Test, Evaluate), a mini plant was designed featuring a bang-bang controller with a 220 VAC water pump as the manipulated variable and a pendulum sensor connected to a 10 kΩ potentiometer. To enable PID control, a proportional valve actuated by an MG995 servo motor was integrated. Experimental results showed the level sensor achieved 97.61% accuracy, 2.86% precision, and 99.83% correlation with a regression model Y = 8.1025X – 12.488. The servo-controlled valve test indicated a flow rate of 21.5844 ml/s at full opening with 1.48% precision and 93.94% correlation (Y = 225.66 – 2.0232X). The module effectively supports PID-based water level control, enhancing laboratory-based process automation education.